(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Timely diagnosis and correctly selected, differentiated, taking into account the stages of treatment of pleural empyema can reduce the length of the patient’s stay in the hospital. The purpose of the study: to study the features of clinical and laboratory parameters in pleural empyema.